The interplay of oxidative stress and immune dysfunction in Hashimoto’s thyroiditis and polycystic ovary syndrome: a comprehensive review - Batóg, Gabriela; Dołoto, Anna; Bąk, Ewelina; Piątkowska-Chmiel, Iwona; Krawiec, Paulina; Pac-Kożuchowska, Elżbieta; Herbet, Mariola (Frontiers in Immunology, 2023)
In recent years, there has been a significant increase in the concomitant incidence of Hashimoto's thyroiditis (HT) and polycystic ovary syndrome (PCOS), both in terms of incidence, etiology, and clinical consequences. PCOS patients suffering from autoimmune thyroid diseases show insulin resistance, impaired glucose tolerance, weight gain, and metabolic and reproductive complications. Studies have shown that chronic stress and its consequence, i.e. oxidative stress, play an important role in the pathomechanism of both disorders. It has also been shown that long-term exposure to stress triggers biological mechanisms, in particular related to the regulation of the inflammatory cascade, which plays a key role in autoimmune diseases. The paper is a review of the literature on the role of chronic stress, oxidative stress, and immune processes in the pathogenesis of HT and PCOS. In addition, the review is a source of knowledge about the treatment of these diseases, and in particular the use of antioxidants in therapeutic management.